The Legal Regulation of Clinical trials on Medicinal Products in the Russian Federation - A. I. Ivanchak; B. A. Kobersky (Московский журнал международного права, 2016)
Clinical trials on medicinal products are regulated not only by the government but also by various international organizations due to the social significance of this problem and the potential risk for human health. Moreover, it is the international acts that provide the basis for the development of the relevant national legislation. The analysis of the aforementioned sources allowed the author to discover the peculiarities of legislative regulation of the clinical trials as well as its dependence on the specific nature of these relationships.